2020
DOI: 10.1680/jbibn.19.00047
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles synthesis using AH leaf extract and its antimicrobial activity

Abstract: Crystallized silver nanoparticles (AgNPs) were synthesized by using the eco-friendly Artocarpus heterophyllus biomaterial. The synthesis of AgNPs was a green approach and a rapid method. The AgNPs were characterized by field-emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy, X-ray diffraction and inductively coupled plasma atomic emission spectroscopy. The FE-SEM analysis showed that the size of the synthesized AgNPs ranged around 45 nm. The plant leaves acted as both a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…To guarantee that the nanoparticles are formed and to evaluate their characteristics, it is fundamental to carry out characterization analyses. The following characterization analyses are widely used: surface plasmon resonance (SPR), to confirm the nanoparticle formation; UV–Vis Spectrophotometer, for monitoring metal ions reduction; FT‐IR, for functional group analysis; scanning electron microscope (SEM) and high‐resolution transmission electron microscope (HR‐TEM) analyses, for determination of size and shape; X‐ray diffractometer analyses, to evaluate its purity and crystalline structure; and thermogravimetric analysis, to monitor weight loss percentage and thermal stability (Botteon et al, 2021; Manjare et al, 2020; Moustafa, 2021; Qayyum et al, 2020; Shanmugapriya et al, 2021; Ulaeto et al, 2020).…”
Section: Future Nanotechnological Therapies For Fungal Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…To guarantee that the nanoparticles are formed and to evaluate their characteristics, it is fundamental to carry out characterization analyses. The following characterization analyses are widely used: surface plasmon resonance (SPR), to confirm the nanoparticle formation; UV–Vis Spectrophotometer, for monitoring metal ions reduction; FT‐IR, for functional group analysis; scanning electron microscope (SEM) and high‐resolution transmission electron microscope (HR‐TEM) analyses, for determination of size and shape; X‐ray diffractometer analyses, to evaluate its purity and crystalline structure; and thermogravimetric analysis, to monitor weight loss percentage and thermal stability (Botteon et al, 2021; Manjare et al, 2020; Moustafa, 2021; Qayyum et al, 2020; Shanmugapriya et al, 2021; Ulaeto et al, 2020).…”
Section: Future Nanotechnological Therapies For Fungal Infectionmentioning
confidence: 99%
“…AgNPs were biosynthesized in another study, using Artocarpus heterophyllus leaf extract, and tested in vitro against some pathogens such as A . niger (Manjare et al, 2020). It is worth mentioning that this plant has antifungal activity and, therefore, its use as a reducing and capping agent is desirable (Manjare et al, 2020; Vázquez‐González, Ragazzo‐Sánchez, & Calderón‐Santoyo, 2020).…”
Section: Future Nanotechnological Therapies For Fungal Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, metal nanoparticles are produced by using either the physiochemical , (Abbas et al, 2019), (Sreedhar, Surendra Reddy, and Keerthi Devi 2009) or green method (Shah et al, 2021), (Gnanadesigan et al, 2011), (Singhal et al, 2011). The biosynthesis of AgNPs using extract of leaves of Artocarpus heterophyllus (Manjare, Paranjape, et al, 2020) and Carissa carandas (Manjare, Sharma, et al, 2020) has been reported.…”
Section: Introductionmentioning
confidence: 99%